Handling of Diarrhea Based on Local Wisdom - Musfirah, Musfirah; Handayani, Sri; Marianche, Vivin (Jurnal Ilmiah Kesehatan (JIKA), 2023)
In Indonesia, around 25,2% of children under 5 years of age die from diarrhea. Diarrhea is still a health problem and is among the top 10 diseases every year. This study aimed to determine the local wisdom-based treatment of diarrhea in toddlers in the working area of ??the Sumarorong Community Health Center, Mamasa Regency, West Sulawesi Province. This type of research used quantitative research with a Cross Sectional Study design to determine local wisdom-based treatment of diarrhea in toddlers in the working area of ??the Sumarorong Community Health Center. The population in this study was all parents of toddlers in the working area of ??the Sumarorong Community Health Center, totaling 120 subjects to using a total sampling.  Technique used logistic regression analysis. Statistically obtained research result showed that there was a relationship between guava leaves intake with a p-value =0,003, bitter tea intake with a p-value=0,000, young jackfruit with a p-value=0,000 on treating diarrhea in the working area of ??the Sumarorong Community Health Center. It is hoped that the community will further increase their knowledge about treating diarrhea based on local wisdom, and dig deeper into information about types of traditional medicine, through more experienced community leaders.